ETHNO-CULTURAL VALUES OF CONCEPTUAL SPHERE OF "GENEROSITY" IN UZBEK AND ENGLISH LANGUAGES (Journal of Science-Innovative Research in Uzbekistan, 2023)
This academic article explores the role of the Uzbek and English languages as  national-cultural values within the conceptual sphere of "Generosity." It delves into  the cultural significance of language and its impact on fostering generosity in Uzbek  and the global community. By examining the linguistic resources, communication  patterns, and cultural practices associated with both languages, we uncover their  contributions to the expression and promotion of generosity within their respective  contexts. This article sheds light on how language serves as a bridge for  understanding, empathy, and acts of kindness, ultimately fostering a culture of  generosity